On Characterizing School Leaders: Evidence from Hindang District, Leyte Division, Philippines - Leomarich F Casinillo; Michael G Suarez (Jurnal Pendidikan Indonesia, 2021)
This study was conducted to characterize school leaders at Hindang District, Leyte Division, Philippines. By complete enumeration, the study considered all active elementary teachers at Hindang District. Primary data was collected through a developed structured questionnaire in regards to the various characteristics of a school leader which serves as an independent variable of the study. On the other hand, secondary data was collected at Department of Education regarding the elementary school classifications at Hindang District as follows: good, better and outstanding. With the aid of ordered logit models, the study highlighted some influencing factors of school classification governed by school leaders. Results showed that on the average, elementary schools in Hindang District are considered to be “better” based on the DepEd classification. This implies that these schools have a room for improvement with the help of an effective school leaders. Based on the constructed ordered logit models, it is shown that a personal attribute of a school leader has an inverse effect in outstanding school classification. In addition, it is revealed that result-focus, teamwork and people development were significant factors in achieving an outstanding performance in school. Hence, a leader must be a results driven that has the ability to create momentum based on their ultimate goal. Furthermore, school leaders must set clear directions, establish expectations since they are in a position to shape the goals, direction and structure of schools.